Coupling of thiols and aromatic halides promoted by diboron derived super electron donors. Issue 88 (20th October 2021) - Franco, Mario; Vargas, Emily L.; Tortosa, Mariola; Cid, M. Belén
Abstract : Diboron-based super electron donors (SEDs) efficiently catalyze the coupling between thiols and aryl halides through a SRN 1 mechanism. Remarkably, under the optimized conditions, the competitive borylation reaction of the aryl halides is suppressed. Abstract : We have proven that pyridine–boryl complexes can be used as superelectron donors to promote the coupling of thiols and aromatic halides through a SRN 1 mechanism. The reaction is efficient for a broad substrate scope, tolerating heterocycles including pyridines, enolizable or reducible functional groups. The method has been applied to intermediates in drug synthesis as well as interesting functionalized polythioethers through a controlled and consecutive intramolecular electron transfer process.